(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
That sustainable development is the best use of resources and wealth manner that does not disturb the destiny of future generations, so research aims to design audit program includes a set of procedures and classified to the dimensions of sustainable development (economic, environmental, social and Institutional) and indicators, to the Ministries of State for ensures policy and strategies control of the State by the parties responsible for control whether internal or external to the achieve needs of current and future generations and development goals